Defensive and Suppressive Measure On Automobile TheftOf Motor Vehicle Centre, Central Investigation Bureau - Sermsutjarit, Warat (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This research article aims to study the problems and obstacles arising from the prevention and suppression of motorcycle theft, and to find solutions to problems and improving procedures for prevention and suppression motorcycle theft by selecting 10 police officers from the Motorcycle Theft Suppression Center, Central Investigation Bureau to conduct the interviews and analyze the data qualitatively. The problem of motorcycle theft prevention and suppression is caused by the lack of manpower in organizing the inspection team, insufficient vehicles for inspection including the amount of CCTV cameras in some areas that cannot be used. The way of solving these problems should be conducted by gathering data from different groups of current motorcycle users and monitoring the movements of motorcycle offenders, increasing the penalty for those who committing illegal acts, also creating applications to provide information and reduce the ordering process. Furthermore, set up a car theft suppression center and publicize it to the public so that they can inform the information directly.